Achtsamkeit in der Psychotherapie: Anwendungen in Forschung und Praxis = Mindfulness in psychotherapy : applications in research and practice - Mander, Johannes; Blanck, Paul (Psychotherapeut, 2018)
Mindfulness is a specific form of attention that is intentional and non-judgmentally focused on the here and now. The roots of mindfulness date back to early Buddhist writings. Mindfulness has been integrated into the two psychotherapy group programs Mindfulness-based Stress Reduction and Mindfulness-Based Cognitive Therapy. The efficacy of these programs, which consist of intensive mindfulness practice during the sessions and at home, is empirically well grounded; however, little research has been carried out on therapeutic applications of mindfulness beyond these group programs and the significance of self-experience in mindfulness for therapists is not clear. This article gives an overview of the various applications of mindfulness and presents the current state of research. Additionally, an approach to training and self-discovery in trainee therapists as a preparation for the implementation of mindfulness into individual therapy is introduced.